Influence of the adoption of information technologies on organizational performance - Valenzuela Fernández, Leslier; Martínez Troncoso, Carolina (Estudios de Administración, 2012)
This research aims to (1) investigate the factors that influence the adoption of IT (2) study the possible influences between IT adoption, organizational performance and perception of quality service by the employees (3) provide empirical evidence through the testing of a descriptive model based on the UTAUT model. The sample consisted of 213 employees of companies of different sizes. We conclude that the use of IT contribute to more efficient use of resources, which would result in better organizational and perception of quality service by employees.